Pelatihan Pembuatan Pupuk Organik Sebagai Bentuk Implementasi Nilai Amar Ma’ruf Nahi Munkar - Nisa', Ihda Shofiyatun; Istiqomah, Nur Hidayatul; Mardiantiningtyas, Namirotus Sholihah; Baidlowi, M (ABDIMASY: Jurnal Pengabdian Kepada Masyarakat, 2024)
The principles of Amar Maroof Nahi Munkar, which emphasize environmental preservation and minimizing reliance on chemical fertilizers, are put into practice through training in the creation of organic fertilizer. The community, particularly farmers and agribusiness actors, receives direct training, counseling, and other forms of support from this non-profit activity (PkM). The program focuses on producing organic fertilizers from agricultural and domestic waste, which is not only more cost-effective and sustainable but also more environmentally benign. The activity's outcomes demonstrated that the training was effective in raising community awareness of the drawbacks of chemical fertilizers and the advantages of adopting organic fertilizers. Additionally, individuals will acquire abilities to independently create organic fertilizer and begin applying it to their farming operations. Here, initiatives to persuade people to reject environmentally harmful farming methods and transition to more sustainable ones are an example of how Amar Maaroof Nahi Munkar's beliefs are being put into effect. As an environmentally responsible and healthier agricultural alternative, it is intended that this activity will further encourage local populations to use organic fertilizer.